234k views
25 votes
I)1-2(2x+1)=1-(x-1)
ii)3.6x-6.1=5.9_2.4x
question from equation and inequality​

1 Answer

8 votes

Answer:

1..
x = -1

2..
x =2

Step-by-step explanation:

Given


i).\ 1-2(2x+1)=1-(x-1)


ii).\ 3.6x-6.1=5.9-2.4x

Solving (i):


1-2(2x+1)=1-(x-1)

Subtract 1 from both sides


1-1-2(2x+1)=1-1-(x-1)


-2(2x+1)=-(x-1)

Open brackets


-4x -2 = -x + 1

Collect Like Terms


x - 4x =2+1


-3x = 3

Divide both sides by -3


x = (3)/(-3)


x = -1

Solving (ii):


3.6x-6.1=5.9-2.4x

Collect Like Terms


2.4x+3.6x=5.9+6.1


6x=12

Divide both sides by 6


x = (12)/(6)


x =2

User Memoizr
by
6.3k points